"VTT"-Domain Proteins VMP1 and TMEM41B Function in Lipid Homeostasis Globally and Locally as ER Scramblases. (June 2021) - Reinisch, Karin M.; Chen, Xiao-Wei; Melia, Thomas J.
Recent studies have identified the metazoan ER-resident proteins, TMEM41B and VMP1, and so structurally related VTT-domain proteins, as glycerolipid scramblases.